4-Methylcyclohexane methanol (MCHM) affects viability, development, and movement of Xenopus embryos. (2021) - Perfetto, Mark; Kirkham, Scotia G.; Ayers, Michael C.; Wei, Shuo; Gallagher, Jennifer E.G.
Graphical abstract: Highlights: MCHM reduces cell viability in vitro that can be partially rescued with antioxidants. MCHM causes immediate and reversible non-responsiveness in Xenopus embryos. When reared in MCHM, Xenopus embryos are underdeveloped and have an increase in melanocyte size and/or migration. Abstract: Following chemical spill disasters, it is important to estimate the effects of spilled chemicals on humans and the environment. Here we analyzed the toxicological effects of the coal cleaning chemical, 4-methylcyclohexane methanol (MCHM), which was spilled into the Elk River water supply in 2014. The viability of HEK293 T human cell line cultures and Xenopus tropicalis embryos was negatively affected, and the addition of the antioxidants alleviated toxicity with MCHM exposure. Additionally, X. tropicalis embryos suffered developmental defects as well as reversible non-responsiveness and melanization defects. The impact MCHM has on HEK293 T cells and X. tropicalis points to the importance of continued follow-up studies of this chemical.